Exosomes: Promising nanocarrier for cancer therapy - Chen‐Chen Zhao; Hui‐Zhong Lv; Su‐Wan Tao; Tong‐Cun Zhang; Na Xu; Lian Zhu (Nano Select, 2022)
Abstract Cancer has intensively threatened the health and life of human beings across the world. Drug delivery systems (DDSs) can protect the packaged cargoes from degradation; effectively delivery cargoes to specific tissues. Most DDSs are based on functional nanomaterials. As natural nanomaterials, exosomes are secreting by mammalian cells through the multivesicle bodies route. Usually, exosomes possess uniform size ranging from 50 to 150 nm, their membrane surface has many functional proteins and cavity contains RNA, DNA similar to maternal cells. Owing to the high biocompatibility, excellent penetration capability as well as ease to be engineered, exosomes have shown outstanding potentials in delivering therapeutic molecules for cancer diagnosis and treatment. This review summarizes the unique characteristics which makes exosomes promising nanocarrier for cancer treatment. The future developments of exosomes based biomedical applications towards cancer are also outlined. We expect the review will help readers understand the potential value of exosomes based nanocarrier, and also try to elaborate their promising applications.